Radiocaesium activity concentrations in parmelioid lichens within a 60 km radius of the Fukushima Dai-ichi Nuclear Power Plant. (August 2015) - Dohi, Terumi; Ohmura, Yoshihito; Kashiwadani, Hiroyuki; Fujiwara, Kenso; Sakamoto, Yoshiaki; Iijima, Kazuki
Abstract: Radiocaesium activity concentrations ( 134 Cs and 137 Cs) were measured in parmelioid lichens collected within the Fukushima Prefecture approximately 2 y after the Fukushima Dai-ichi Nuclear Power Plant accident. A total of 44 samples consisting of nine species were collected at 16 points within a 60 km radius of the Fukushima Dai-ichi Nuclear Power Plant. The activity concentration of 134 Cs ranged from 4.6 to 1000 kBq kg −1 and for 137 Cs ranged from 7.6 to 1740 kBq kg −1 . A significant positive correlation was found between the 137 Cs activity concentration in lichens and the 137 Cs deposition density on soil ( n = 44), based on the calculated Spearman's rank correlation coefficients as r = 0.90 ( P < 0.01). The two dominant species, Flavoparmelia caperata ( n = 12) and Parmotrema clavuliferum ( n = 11), showed strong positive correlations, for which the r values were calculated as 0.92 ( P < 0.01) and 0.90 ( P < 0.01) respectively. Therefore, Flavoparmelia caperata and Parmotrema clavuliferum are suggested as biomonitoring species for levels of radiocaesium fallout within the Fukushima Prefecture. Highlights: 134 Cs and 137 Cs in 9 parmelioid lichen species in Fukushima Pref. were determined. 134 Cs and 137 Cs in these species ranged 4.6–1000 and 7.6–1740 kBq kg −1 . 137 Cs in these species was positively correlated with 137 Cs inventory in soil. Flavoparmelia caperata and Parmotrema clavuliferum were dominated species. Significant difference of 137 Cs accumulation level in the two species was observed.